Transcriptome Analysis of Melocactus glaucescens (Cactaceae) Reveals Metabolic Changes During in vitro Shoot Organogenesis Induction - Torres-Silva, Gabriela; Correia, Ludmila Nayara Freitas; Batista, Diego Silva; Koehler, Andréa Dias; Resende, Sheila Vitória; Romanel, Elisson; Cassol, Daniela; Almeida, Ana Maria Rocha; Strickler, Susan R.; Specht, Chelsea Dvorak; Otoni, Wagner Campos (Frontiers in Plant Science, 2021)
Melocactus glaucescens is an endangered cactus highly valued for its ornamental properties. In vitro shoot production of this species provides a sustainable alternative to overharvesting from the wild; however, its propagation could be improved if the genetic regulation underlying developmental processes were known. The present study generated de novo transcriptome data, describing in vitro shoot organogenesis induction in M. glaucescens. Total RNA was extracted from explants before (control) and after shoot organogenesis induction (treated). A total of 14,478 unigenes (average length, 520 bases) were obtained using Illumina HiSeq 3000 sequencing and transcriptome assembly. Filtering for differential expression yielded 2,058 unigenes. Pairwise comparison of treated vs. control genes revealed that 1,241 (60.3%) unigenes exhibited no significant change, 226 (11%) were downregulated, and 591 (28.7%) were upregulated. Based on database analysis, more transcription factor families and unigenes appeared to be upregulated in treated samples than in controls. Expression of WOUND INDUCED DEDIFFERENTIATION 1 (WIND1) and CALMODULIN (CaM) genes, both of which were upregulated in treated samples, was further validated by RT-qPCR. Differences in gene expression patterns between control and treated samples indicate substantial changes in primary and secondary metabolism of M. glaucescens after the induction of shoot organogenesis. These results help to clarify the molecular genetics and functional genomic aspects underlying propagation in the Cactaceae family.